Collapsing the Surfaces of Skin and Photograph in Cosmetic Minimally-Invasive Procedures. (June 2018) - Hurst, Rachel Alpha Johnston
This article proposes that cosmetic minimally-invasive procedures – Botox injections, soft-tissue fillers, microdermabrasion, chemical peels and laser treatments – are an under-researched area and provide a number of promising paths for skin studies research. I argue that cosmetic minimally-invasive procedures collapse the difference between the surfaces of the photograph and the skin – the primary surfaces of cosmetic surgery – more successfully than cosmetic surgical procedures. More precisely, I maintain that the difference between photograph and skin is collapsed in two ways: first, through narrating the transformation of the skin's surface in a way that more closely matches the photographic promises of the cosmetic surgery industry; and, second, by depicting the surgical penetration of the skin through advertising photography. The article concludes by suggesting that further investigation into cosmetic minimally-invasive procedures could offer a new way to think about relationships between 'normative' and 'non-normative' skin modification practices.